2018
DOI: 10.1002/macp.201800444
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of Poly(Vinyl Amine) with Acetone in Water

Abstract: Poly(vinyl amine) (PVAm) reacts with acetone in aqueous solution. It generates imine and aminal moieties along the PVAm backbone. The molecular structure of acetone‐modified PVAm is confirmed by liquid 1H and 13C as well as solid state 13C NMR and ATR‐FTIR spectroscopies. Model compounds produced from 1,3‐diaminopropane with acetone in chloroform are used to assign the solid state 13C NMR signals of the modified polymer. Quantitative elemental analysis of acetone‐modified PVAm samples supports the analytical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The final weight loss at 1000 C was observed to be 76.7%. On the other hand, four thermal degradation steps were observed for the samples taken at the 8th, and 12th h of the hydrolysis reaction of PNVF in basic medium at F I G U R E 5 (a) Mechanism for the base hydrolysis of PNVF proposed by Witek et al, 49 (b) suggested reactions of PVAm with acetone to imine and aminal derivative structures proposed by Trommler et al 54 similar temperature ranges but different weight loss values. The first degradation steps for samples taken at 8th and 12th h were observed between 100-150 C with 4.3, and 2.9% weight losses, the second degradation steps were observed between 250-370 C with 38.3, and 45.4% weight losses, third degradation steps were observed between 625-670 C with 59.0, and 73.8% weight losses, and the fourth degradation steps were observed between 830-950 C with 76.5%, and 92.5% weight losses, respectively.…”
Section: Characterization Of Hydrolysis Productsmentioning
confidence: 93%
See 2 more Smart Citations
“…The final weight loss at 1000 C was observed to be 76.7%. On the other hand, four thermal degradation steps were observed for the samples taken at the 8th, and 12th h of the hydrolysis reaction of PNVF in basic medium at F I G U R E 5 (a) Mechanism for the base hydrolysis of PNVF proposed by Witek et al, 49 (b) suggested reactions of PVAm with acetone to imine and aminal derivative structures proposed by Trommler et al 54 similar temperature ranges but different weight loss values. The first degradation steps for samples taken at 8th and 12th h were observed between 100-150 C with 4.3, and 2.9% weight losses, the second degradation steps were observed between 250-370 C with 38.3, and 45.4% weight losses, third degradation steps were observed between 625-670 C with 59.0, and 73.8% weight losses, and the fourth degradation steps were observed between 830-950 C with 76.5%, and 92.5% weight losses, respectively.…”
Section: Characterization Of Hydrolysis Productsmentioning
confidence: 93%
“…52,53 It is reported that amidine groups can be formed when PNVF-co-PVAm copolymers with PVAm content are of the order of 20%-80%, which is more common in acidic hydrolysis. 54 Witek et al performed detailed 13 C NMR spectroscopy studies to explain the mechanism of basic hydrolysis of PNVF and possible side reactions most likely to occur. They reported that the chemical shift of transient amidine ring appears and then vanishes with the progress of basic hydrolysis of PNVF.…”
Section: Characterization Of Hydrolysis Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the precipitated hydrogel exhibited two characteristic new signals at 67 ppm (minor) and 75 ppm (major), which were, by comparison with the chemical shifts of the aminals in solution and the solid state, assigned to hemiaminal and aminal cross-links, respectively (Figure d). Imine formation shown by chemical shifts of the involved carbon atoms at 165 ppm , is not found, which is indirectly seen by the comparison of spectra in Figure c,d and Figure S3.…”
mentioning
confidence: 83%
“…To this end, acylhydrazines , and most recently triketones appear promising but are only available at an increased synthetic cost. Polyvinylamine (PVAm) is a simple, yet highly functionalized and water-soluble polymer known for paper-making, wastewater treatment, and superabsorber materials. , PVAm undergoes a number of reactions as a nucleophilic reagent with epoxides, aldehydes, isocyanates, or electron-deficient aromatics. Ketones, which are considered to be generally less toxic but also less electrophilic than aldehydes, do not rapidly react with amines in water, with PVAm being an exception . Notably, the use of PVAm for dynamic network formation remains unexplored.…”
mentioning
confidence: 99%